Glass encapsulation of molecular-doped epitaxial graphene for quantum resistance metrology. (1st November 2022) - Park, Jaesung; Lim, Kyung-Geun; Chae, Dong-Hun
Abstract: The large Landau energy spacing, stemming from the linear energy-momentum dispersion of quasi-particles in graphene, allows an efficient realization of the quantum Hall effect at a small density of charge carriers. Promising scalable epitaxial graphene on silicon carbide (SiC), however, requires molecular doping, which is generally unstable under ambient conditions, to compensate for electron transfer from the SiC substrate. Here, we employed classical glass encapsulation common in organic electronics to passivate molecular-doped epitaxial graphene against water and oxygen molecules in air. We have investigated the stability of Hall quantization in a glass-encapsulated device for almost 1 year. The Hall quantization is maintained above a threshold magnetic field within 2 nΩ Ω −1 smaller than the measurement uncertainty of 3.5 nΩ Ω −1 through multiple thermal cycles for almost 1 year, while the ordinary unencapsulated device in air distinctly shows a relative deviation larger than 0.05% from the nominal quantized Hall resistance in 1 month.